Thermo-mechanical assessment of silver sintering for attaching power components in embedded PCB. (November 2020) - Arabi, F.; Youssef, T.; Coudert, M.; Coquery, G.; Alayli, N.; Martineau, D.; Belnoue, O.
Abstract: PCB-Embedding technology is an established approach for the miniaturization of electronic systems and modules. Silver sintering, which is a reliable alternative to Lead-Free Bonding, is used to assemble the embedded power components in the PCB. Thermal cycles [−25 °C/+125 °C] have highlighted degradations in the die attach. The shear strength of dice decreases from 4 MPa before cycling to 2 MPa at 1040 cycles. The junction temperature has drifted during cycling especially at high temperatures. Simulations have shown that the maximal stresses are in the preg materials. This suggests cracks of the preg during the experiments. Simulations showed also a concentration of plastic stresses on the die attaches. The accumulation of stresses increases during aging. The presented methodology of thermal cycling simulation represents a good way to estimate the lifetime of embedded PCB. Highlights: Presentation of embedded PCB sintering process and its validation Assessment of embedded PCB state of health during thermal cycling Evaluation of junction temperature and shear strength measurement evolution upon aging Investigation of sintered silver die attach using scanning acoustic microscopy Development of multiphysics model able to quantify the strain energy density accumulation during cycling